(untitled) (Al-Academy, 2018)
The art of postmodernism has undergone a number of changes in the course of art and art schools, as art has left the traditional means and paved the way for this artistic transformation to change the materials, techniques, methods and visions as a result of the changes that occurred in the thought and this change played an important role in the artist’s vision, To demolish and destroy all of the above and to reconsider the formal systems and intellectual contexts and expressive modes, so it is necessary for the whole art to keep up with the variables of the era and its elements. The current research aims to: "Detect the transformations of form in postmodern art in the projects of students of the Department of Art Education". Since the current research aims at detecting the transformations of postmodern art in the projects of the students of the Department of Art Education, the researcher followed the descriptive method of method (analysis of content) to analyze the sample of the research being the most appropriate scientific curriculum to achieve the goal of research. The current research community consists of the projects of the students of the Department of Art Education, which were completed by students of the fourth grade morning for the academic year (2016-2017), which are (15) artistic products in the field of painting implemented abstract expressionist methods. An objective sample was chosen from the projects of the fourth grade students, the Department of Art Education reached (4) works of art bearing abstract expressionist methods. The research came out with a number of results, the most important of which are: 1-The student’s use of pieces of clothing (shirt) as he transformed the realistic form of wearing the shirt into a abstract expression form, as in sample(1). 2-The student’s use of various techniques represented by collage technology, and used newspaper clips in a coordinated and coordinated manner and using the technique of liquefaction (showing the color on the surface) to show the work in a streamlined manner, resulting in a shift in shape, as in sample(2).